Peningkatan Keterampilan Hidup Pemuda Putus Sekolah Melalui Pelatihan Instalasi Listrik dan Pelaporan Sederhana Keuangan Usaha - Maharani Purba, Angelia; Purba, Arlina Pratiwi; Simatupang, Eva Malina; Imnadir, Imnadir; Saputro, Ngairan Banu (Politeknik Negeri Medan, 2023)
Residential electrical installation training aims to improve skills, especially for those who have dropped out of school. Those who drop out of school need capital to find work for survival. The method used is to provide a basic theory of electrical installation and direct practice in the modules provided by the proposer using multiplexes at PKBM Hanuba. In addition, training was also given in making simple financial reports. Training is helpful for students to make simple financial reports from the products they make and will market namely acrylic flowers. The result of this activity is that students gain soft skills and hard skills that can be used for life skills, including being able to draw electrical designs for simple residential homes, being able to install simple residential electrical installations, being able to maintain electrical installations for simple residential homes, and being able to implement K3 in the implementation of the installation.